Participatory Design and Evaluation of the "Stem Cells Australia" Website for Delivering Complex Health Knowledge: Mixed Methods Study - Patrick Cheong-Iao Pang; Megan Munsie; Shanton Chang; Claire Tanner; Christine Walker (JMIR Publications, 2023)
BackgroundThe internet has become a commonly used information source for people seeking to understand their health care options. However, inconsistent representation about what stem cell treatments are available and from whom, coupled with the lack of transparency about what has been shown to work or is even safe, can distract and mislead users. Given these challenges, there is a need to develop effective evidence-based tools for delivering information about health care options involving stem cells. ObjectiveA need to redesign an existing website in Australia was identified to provide trustworthy information about stem cell research and to counter misinformation. Using a participatory design approach to generate an understanding of what information users need for stem cell treatments, the Stem Cells Australia website serves as a case study for the development and evaluation of websites delivering complex messages about science and health. MethodsThis study comprised 3 steps. First, a focus group and several one-on-one interviews with a purposive sample of users (n=12) were conducted to identify their needs and requirements. Second, we designed a new version of the website based on findings from the focus group and interviews. Finally, for evaluating the participatory design process, we collected 180 days of Google Analytics data for both the original and redesigned versions (90 days for each) and compared their differences using 2-sample z tests. ResultsThe feedback from participants was grouped into 3 themes-needed and unwanted information, how and where to obtain information, and their information preferences. These were translated into requirements for rebuilding the website. The redesigned version reached users in other continents, despite the daily numbers of users (−61.2%; P<.001) and sessions (−61.7%; P<.001) decreasing. The redesigned version also showed substantial decrease in daily bounce rate (−97.2%; P<.001), significant increase in the daily average of page reads per session (+110.8%; P<.001), and long daily average for session duration (+22.9%; P=.045). Navigation flow analysis showed more traffic toward web pages related to health conditions in the redesigned version. ConclusionsWebsites about stem cell research need to provide content for vulnerable global audiences. Participatory design that addresses knowledge gaps and information needs can produce better performance and engagement, which can be evaluated using Google Analytics, a common web analytics tool used by many websites. Learnings for improving the metrics regarding website identity, research updates, and clinical trials are concluded, which can inform the future design of websites seeking to engage users and provide reliable and accessible science and health information including but not limited to stem cell research and therapies.